"Once you open that door, it's a floodgate": Exploring work-related grief among community service workers providing care for structurally vulnerable populations at the end of life through participatory action research. (April 2023) - Giesbrecht, Melissa; Mollison, Ashley; Whitlock, Kara; Stajduhar, Kelli I
Background: At the end of life, people experiencing structural vulnerability (e.g. homelessness, poverty, stigmatization) rely on community service workers to fill gaps in access to traditional palliative services. Although high levels of burnout are reported, little is known about these workers' experiences of grief. Aim: To explore community service workers' experiences of grief to identify ways of providing more tailored, meaningful, and equitable supports. Design: A community-based participatory action research methodology, informed by equity perspectives, was employed. Setting/participants: In an urban center in western Canada, community service worker (primary) participants ( n = 18) were engaged as members of an action team. A series of 18 action cycles took place, with secondary participants ( n = 48) (e.g. palliative, social care, housing support, etc.) being recruited throughout the research process. Focus groups ( n = 5) and evaluative interviews ( n = 13) with participants were conducted. Structured observational field notes ( n = 34) were collected during all team meetings and community interventions. Interpretive thematic analysis ensued through a collaborative and iterative process. Results: During initial meetings, action team participants described experiences of compounding distress, grief, and multiple loss. Analysis showed workers are: (1) grieving as family, not just providers; (2) experiencing complex layers of compounded grief; and (3) are fearful to open the "floodgates" to grief. Conclusions: Findings contribute to our understanding on the inequitable distribution of grief across society. A collective and material response is needed, including witnessing, acknowledging and valuing the grief process; facilitating community wellness, collective grieving, and advocacy; and providing training and tools in a palliative approach to care.